Frequency and plasma condition dependent spatial structure of low frequency global potential oscillations in the TJ-II stellarator. (5th March 2019) - Kobayashi, T.; Losada, U.; Liu, B.; Estrada, T.; van Milligen, B.Ph.; Gerrú, R.; Sasaki, M.; Hidalgo, C.
Abstract: In this letter, we investigate the spatial structure of a low frequency global potential oscillation, which is likely ascribed as the low frequency zonal flows, in TJ-II laboratory plasmas. In two plasmas produced by different heating schemes (electron cyclotron resonance heating and neutral beam injection heating) and characterized by different mean radial electric field structures, frequency-space-decomposed spectra of the global potential oscillation are obtained. In both cases, the oscillatory field has a single-peaked potential structure and a dipole radial electric field structure. The oscillating structure depends on its frequency as well as on the heating scheme.